Enhanced proton conductivity of Gd-Co bi-doped barium cerate perovskites based on structural and microstructural investigations - Accardo, G.; Frattini, D.; Yoon, S. P. (ELSEVIER SCIENCE SA, 2020)
Microstructural and electrochemical investigations of bi-doped (Gd and Co) barium cerate perovskites, with theoretical formula BaCe(0.85-x)CoxGd0.15O3-delta (x = 0.02; 0.03 and 0.05) were carried out by X-ray Diffraction (XRD), Rietveld refinement, scanning electron microscopy (SEM), Raman, X-ray photoelectron spectroscopy (XPS), and electrochemical impedance spectroscopy analysis (EIS). Based on the ionic radii of Co2+ (0.75 angstrom) and Co3+ (0.55 angstrom, six-fold coordination), Co ions did not substitute Ba ions on the A-sites of the ABO 3 perovskite and therefore substituted Ce ions on the B-sites. The behavior was confirmed by Raman analysis where it was found that cobalt doping stabilized the perovskite arrangement favoring a higher symmetry structure. From the XPS analysis, an increase in oxygen vacancies as the surface defect for proton conduction was detected in the samples with higher cobalt content. These samples showed the highest proton conductivity of 4.81.10(-3)-4.36.10(-2) S cm(-1) in the temperature range 200-800 degrees C. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: OXIDE FUEL-CELLS; ELECTRICAL-PROPERTIES; IONIC-RADII; NEUTRON-DIFFRACTION; CHEMICAL-STABILITY; BACEO3; TEMPERATURE; ELECTROLYTES; PHASE; CU